Question
upstudy study bank question image url

3 a, bet \( c \) sont des nombres rationnels non nuls. Simplifier : \( 4\left(a^{-1}\right)^{6} ; \frac{5}{3} a \times \frac{-2}{25} a^{-2} ; \frac{7}{2} a^{4} \times \frac{2}{21} a^{-2} \times\left(-3 a^{-3}\right) \) \( c^{-3} \times b\left(a c^{2}\right)^{-2} \times a^{-4} \times b^{2} \quad ; \quad(3 a)^{3} \times\left(\frac{1}{a}\right)^{-2} \times\left(\frac{a}{2}\right)^{-3} \)

Ask by Nguyen Logan. in Morocco
Jan 09,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

1. \( \frac{4}{a^{6}} \) 2. \( \frac{-2}{15a} \) 3. \( -\frac{1}{a} \) 4. \( \frac{b^{3}}{a^{6} c^{7}} \) 5. \( 216 a^{2} \)

Solution

Bien sûr, simplifions chaque expression une par une. ### 1. \( 4\left(a^{-1}\right)^{6} \) Appliquons la règle des puissances : \[ 4\left(a^{-1}\right)^{6} = 4 \cdot a^{-6} = \frac{4}{a^{6}} \] ### 2. \( \frac{5}{3} a \times \frac{-2}{25} a^{-2} \) Multipliant les coefficients et les puissances de \( a \) : \[ \frac{5}{3} \times \frac{-2}{25} = \frac{-10}{75} = \frac{-2}{15} \] \[ a \times a^{-2} = a^{1-2} = a^{-1} = \frac{1}{a} \] Ainsi, le produit est : \[ \frac{-2}{15} \times \frac{1}{a} = \frac{-2}{15a} \] ### 3. \( \frac{7}{2} a^{4} \times \frac{2}{21} a^{-2} \times (-3 a^{-3}) \) Multipliant les coefficients : \[ \frac{7}{2} \times \frac{2}{21} \times (-3) = \frac{14}{42} \times (-3) = \frac{1}{3} \times (-3) = -1 \] Multipliant les puissances de \( a \) : \[ a^{4} \times a^{-2} \times a^{-3} = a^{4-2-3} = a^{-1} = \frac{1}{a} \] Ainsi, le produit est : \[ -1 \times \frac{1}{a} = -\frac{1}{a} \] ### 4. \( c^{-3} \times b(a c^{2})^{-2} \times a^{-4} \times b^{2} \) Simplifions chaque facteur : \[ (a c^{2})^{-2} = a^{-2} c^{-4} \] Ainsi, l'expression devient : \[ c^{-3} \times b \times a^{-2} c^{-4} \times a^{-4} \times b^{2} \] Regroupons les termes semblables : \[ a^{-2} \times a^{-4} = a^{-6} \] \[ b \times b^{2} = b^{3} \] \[ c^{-3} \times c^{-4} = c^{-7} \] Donc, l'expression simplifiée est : \[ a^{-6} b^{3} c^{-7} = \frac{b^{3}}{a^{6} c^{7}} \] ### 5. \( (3 a)^{3} \times \left(\frac{1}{a}\right)^{-2} \times \left(\frac{a}{2}\right)^{-3} \) Simplifions chaque facteur : \[ (3a)^{3} = 27 a^{3} \] \[ \left(\frac{1}{a}\right)^{-2} = a^{2} \] \[ \left(\frac{a}{2}\right)^{-3} = \left(\frac{2}{a}\right)^{3} = 8 a^{-3} \] Multipliant tous les termes : \[ 27 a^{3} \times a^{2} \times 8 a^{-3} = 27 \times 8 \times a^{3+2-3} = 216 a^{2} \] **Résultat final :** \[ 216 a^{2} \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

Pour simplifier l'expression \( 4\left(a^{-1}\right)^{6} \), on commence par élever \( a^{-1} \) à la puissance 6, ce qui donne \( a^{-6} \). En multipliant par 4, on obtient \( 4 a^{-6} \). Pour \( \frac{5}{3} a \times \frac{-2}{25} a^{-2} \), on multiplie les coefficients : \( \frac{5 \times (-2)}{3 \times 25} = \frac{-10}{75} = -\frac{2}{15} \). Ensuite, on additionne les exposants de \( a \) : \( a^{1 - 2} = a^{-1} \). L'expression simplifiée est donc \( -\frac{2}{15} a^{-1} \). Pour \( \frac{7}{2} a^{4} \times \frac{2}{21} a^{-2} \times\left(-3 a^{-3}\right) \), premièrement, en multipliant les coefficients : \( \frac{7 \times 2 \times (-3)}{2 \times 21} = \frac{-42}{42} = -1 \). Ensuite, pour \( a \), on additionne : \( a^{4 - 2 - 3} = a^{-1} \). Par conséquent, nous avons \( -1 \cdot a^{-1} = -a^{-1} \). Pour \( c^{-3} \times b\left(a c^{2}\right)^{-2} \times a^{-4} \times b^{2} \), on va d'abord traiter \( (a c^{2})^{-2} = a^{-2} c^{-4} \). Ensuite, en multipliant tout ensemble, on réunit les coefficients et les puissances : \( c^{-3} \times b \times a^{-2} c^{-4} \times a^{-4} b^{2} = b^{3} a^{-6} c^{-7} \). Enfin, dans \( (3 a)^{3} \times\left(\frac{1}{a}\right)^{-2} \times\left(\frac{a}{2}\right)^{-3} \), on a \( (3^3 a^3) \) soit \( 27 a^3 \) avec \( a^{2} \) qui devient \( a^{2} \) en multipliant par \( 27 a^{3} \). Cela nous donne \( 27 a^{5} \). Pour \( \left(\frac{a}{2}\right)^{-3} = \frac{2^3}{a^{3}} = \frac{8}{a^{3}} \). En multipliant tout cela à la fin, nous obtenons \( 216 a^{2} = 216a^{2} \). En résumé, les expressions simplifiées sont : - \( 4 a^{-6} \) - \( -\frac{2}{15} a^{-1} \) - \( -a^{-1} \) - \( b^{3} a^{-6} c^{-7} \) - \( 216 a^{2} \)

Related Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy